2020
DOI: 10.1177/2150132720955026
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian Health Care Workers’ Stress and Stressors During COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Background: COVID-19 is thought to be the most significant public health threat the modern world has encountered. Health care workers (HCWs) face enormous pressure due to work overload, negative emotions, exhaustion, lack of contact with their families, and risk of catching the infection and death. Aim: This study aims to assess the level of stress perceived by HCWs and possible associated factors during the COVID-19 outbreak in Palestine. Methods: A cross-sectional sample of 430 frontlines HCWs was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 21 publications
6
69
0
1
Order By: Relevance
“…Similarly, HCW during the SARS outbreak who had confidence in the information they received from their organization ( 130 ), and who received clear communication about directives and how to take precautionary measures ( 41 ), experienced reduced psychological distress. HCW working during the COVID-19 outbreak who felt that they did not receive sufficient information, scored significantly higher on anxiety and acute stress than those who were satisfied with the information provided ( 60 , 99 , 116 , 142 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, HCW during the SARS outbreak who had confidence in the information they received from their organization ( 130 ), and who received clear communication about directives and how to take precautionary measures ( 41 ), experienced reduced psychological distress. HCW working during the COVID-19 outbreak who felt that they did not receive sufficient information, scored significantly higher on anxiety and acute stress than those who were satisfied with the information provided ( 60 , 99 , 116 , 142 ).…”
Section: Resultsmentioning
confidence: 97%
“…In nurses working during the SARS outbreak in Canada, higher perceived organizational support in the form of receiving positive performance feedback from doctors and co-workers, was associated with lower perceptions of SARS-related threat and reduced feelings of emotional exhaustion ( 59 ). Similarly, nurses, physicians, and HCW working during the MERS, COVID-19, and SARS outbreaks who perceived support from their supervisors and colleagues, experienced better mental health in the form of lower PTSD symptoms, lower distress, and being less likely to develop psychiatric symptoms, respectively ( 24 , 28 , 41 , 54 , 59 , 70 , 79 , 80 , 88 , 99 , 116 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies identified specific coping mechanisms employed by HCWs during the pandemic (Blanco-Donoso et al ., 2020; Cai, 2020; Chen et al ., 2020; Chew et al ., 2020; Dong et al ., 2020; Giusti et al ., 2020; Labrague & De los Santos, 2020; Maraqa et al ., 2020; Mi et al ., 2020; Nie et al., 2020; Salman et al, 2020; Shechter et al ., 2020; Vagni et al ., 2020; Xiao et al ., 2020). During the pandemic, HCWs utilized both negative and positive coping styles to manage stress.…”
Section: Methodsmentioning
confidence: 99%
“…Among these ten studies reporting specific coping styles among HCWs during the pandemic, eleven quantitative studies (Cai, 2020; Blanco-Donoso et al ., 2020; Chew et al ., 2020; Dong et al ., 2020; Giusti et al ., 2020; Labrague & De los Santos, 2020; Nie et al ., 2020; Xiao et al ., 2020; Chen et al ., 2020; Maraqa et al ., 2020; Vagni et al ., 2020) indicated that HCWs use support from and communication with family, friends, and colleagues as their primary coping mechanisms to manage the adverse mental health consequences of the COVID-19 pandemic. Religious coping mechanisms such as praying were reported as an important coping mechanism in three cross-sectional studies.…”
Section: Methodsmentioning
confidence: 99%